PENGARUH PAJAK DAERAH, RETRIBUSI DAERAH, DAN PERTUMBUHAN EKONOMI TERHADAP PENDAPATAN ASLI DAERAH - Pieter Christian (2017)
The purpose of this study was to examine the influence of local taxes, charges, and economic growth to local revenue. The independent variables in this study is local taxes , charges and economic growth. The dependent variable in this study is the local own revenues, with years of research for 2012-2014. The sample used in this study is the districts/cities in West Java, Middle Java and East Java. The samples taken by proporsional cluster sampling method. Samples were obtained in this study amounted to 90. After eliminating the data outliers, ultimately resulting in 76 samples were prepared and tested in the analysis. This study uses multiple linear regression analysis. The results from this study indicate that the local taxes ,charges have significant effect and economic growth have a negative significant effect to local own revenues.